Aplication of CO2 cooling for blow moudling process - Brdlík, Pavel (Univerzita Pardubice, 2012)
The mould blowing process is the third most used technology for the production of plastic products on the world. These products are characterized by complex hollow shapes and are used for example in the packaging, transportation, pharmaceutical and automotive industries. With the ongoing growth of these industries, increasingly higher demands are being made on optimizing production. Hence, much work is being focused on these problems. The present article deals with optimizing the cooling systems. It is necessary to emphasize the importance of this part of the blow moulding process since cooling time in relation to the value, thickness, shape, material, etc. of the product can represent 80% of the time in the production cycle. The optimization was made cooperation conventional cooling system with system injection of liquid CO2 into internal parts of product. It was explored and discussed variants of implementation, so optimal batching. A proper attention was given evaluation cooling ability of system. Results are showed that CO2 system could increase cooling efficiency as products small volumes as products large volumes. The improve productivity examined group of product was got in range 17 % – 24 %. It was also proved that increase speed of cooling didn´t influence used behavior of products.
Keywords: mould blowing process; plastic products; optimizing; cooling systems